Characterization of Bond-Slip Behaviour of the Profiled Steel Sheet Dry Board (PSSDB) Composite System - Roslan, Aina Syafawati; A. Majid, Masni; Jaini, Z. M.; Sutiman, Nur Adidah (International Journal of Integrated Engineering, 2021)
This paper presents an experimental study on the shear connector performance of the profiled steel sheet dry board (PSSDB) composite system through the push-out test. The load-slip curve can be obtained from the push-out test where the system reaches its failure point in which the stiffness value was determined. Ten push-out tests were carried out using different connector spacing ranging from 50–250mm. Two types of profiled steel sheets with a thickness of 1mm were used meanwhile, dry board with 16mm thickness were set as constant. From the result, it can be concluded that the connector spacing plays a major role in influencing the stiffness of the PSSDB system compared to the profiled steel sheet types. The selection of suitable connector spacing is essential in determining the shear performance of the specimen. The specimen with 50mm connector spacing has the highest maximum load, which indicates a high stiffness value. However, it is recommended that the spacing of 100-200mm are used to avoid accelerate failure and ultimately more practical and economical.